2019
DOI: 10.1007/s42380-019-00038-2
|View full text |Cite
|
Sign up to set email alerts
|

School Climate Counts: A Longitudinal Analysis of School Climate and Middle School Bullying Behaviors

Abstract: The purpose of the current study was to investigate whether student perceptions of school climate were associated with traditional and cyber bullying participant behaviors over the course of a school year. Additionally, gender was explored as a moderator in the associations between school climate perceptions and bullying participant behaviors. Data were collected from 870 6th through 8th grade middle school students using the Bullying Participant Behaviors Questionnaire (BPBQ;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 46 publications
3
22
0
1
Order By: Relevance
“…An association between SC and BP has also been demonstrated [10], as well the link between SC and school violence [9,29]. In line with this, the research has shown that a decline in SC is related to higher BP at school [30], which include telling lies and breaking rules [31] and externalizing behaviors [3], or even in the increase of absenteeism [27]. Research has shown that inadequate characteristics of the physical environment (e.g., inadequate lighting, hiding places, gang-related or hate-related graffiti, inadequate supervision of corridors, and poor maintenance) can create opportunities for conflict and violence and foster tolerance for aggressive behavior [32].…”
Section: Relationships Between School Climate Behaviour Problems Andmentioning
confidence: 57%
See 2 more Smart Citations
“…An association between SC and BP has also been demonstrated [10], as well the link between SC and school violence [9,29]. In line with this, the research has shown that a decline in SC is related to higher BP at school [30], which include telling lies and breaking rules [31] and externalizing behaviors [3], or even in the increase of absenteeism [27]. Research has shown that inadequate characteristics of the physical environment (e.g., inadequate lighting, hiding places, gang-related or hate-related graffiti, inadequate supervision of corridors, and poor maintenance) can create opportunities for conflict and violence and foster tolerance for aggressive behavior [32].…”
Section: Relationships Between School Climate Behaviour Problems Andmentioning
confidence: 57%
“…The present study has as main purpose to analyze the mediating effect of PI on the relationships between SC and BP, taking into consideration the school personnel perceptions, a topic that has not been previously studied in the Portuguese context. Similarly, and despite the existence of several international studies focused on these variables proving the existence of a positive relationship SC and BP (e.g., [2,10,29,30,44]) and between SC and PI (e.g., [20,23]), demonstrating that the educational and relational practices of school are important predictors of successful results [42] or even that PI increase social functioning [40] and could yet reduce other problems behaviors (i.e., dropout and substance use) [21], research about mediators is sparce. This study is expected to represent a relevant contribution to the understanding of this phenomenon and to contribute to the development of other studies in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This axis is directly associated with the studio of the second line (student). Here, mainly, the aspects of the educational centre are examined as a space where this type of aggression begins [134] (bullying victimization, child safety, computer, cultural factor, ethnicity, or high school student).…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…The first criteria characterizing bullying is "aggressive behavior or intentional harm doing", secondly, bullying is "repeatedly and over time" and third, "in an interpersonal relationship characterized by an imbalance of power". Authors in literature argue, that students who were bullied and also bully, »reported low academic achievement, loneliness, and psychosocial maladjustment« (Nansel et al 2001;in Dorio et al, 2019).…”
mentioning
confidence: 99%